2022
DOI: 10.14293/s2199-1006.1.sor-.pp2ke4y.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly of Neuroscience to the model of mind

Abstract: Currently, there are several mind models developed as cognitive architectures and their main focus is to explain mind functions. However, few architectures explain the neural basis of the mind. Also, neuroscience explains the neural basis of the brain and is directly related to the mind. The study objective was to identify a mind model with a neural basis established in the model. Therefore, the study uses a systematic review of existing literature to find a mental model with a neural basis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…These results are consistent with experimental studies on effluent from reverse-osmosis of drinking water (Imbulana et al 2020), and on studies of CKDu in Moneragala, Sri Lanka (Liyanage et al 2022) where higher concentrations of Mg 2+ & Fions were found in CKDu-associated water sources. In contrast, a factor-analysis study (Paranagama etal 2018) claimed stronger correlation between F -& Na + than with F -& Mg ++ in CKDu-linked water sources.…”
Section: Impurities In Fertilizerssupporting
confidence: 90%
“…These results are consistent with experimental studies on effluent from reverse-osmosis of drinking water (Imbulana et al 2020), and on studies of CKDu in Moneragala, Sri Lanka (Liyanage et al 2022) where higher concentrations of Mg 2+ & Fions were found in CKDu-associated water sources. In contrast, a factor-analysis study (Paranagama etal 2018) claimed stronger correlation between F -& Na + than with F -& Mg ++ in CKDu-linked water sources.…”
Section: Impurities In Fertilizerssupporting
confidence: 90%